Comparative Study of Financial Performance of Issuers on Indonesian Stock Exchange during and after Merger and Acquisition Strategy - Sudibyo, Adityatama; Akbar, Aldi (PT. Riset Press International, 2024)
The merger and acquisition strategy has become the main choice of large companies in improving their financial performance and improving their position in the market. This study aims to determine the effect of merger and acquisition strategies on the financial performance of companies on the Indonesia Stock Exchange. This study uses a quantitative approach with a population of companies that conduct mergers and acquisitions on the Indonesia Stock Exchange from 2018 to 2022. Data was collected from the company's financial statements and analysis was carried out using financial ratios such as Current Ratio, Total Assets Turnover Ratio, Debt to Equity Ratio, and Return on Equity The results showed that the merger and acquisition strategy had no significant effect on the financial performance of companies on the Indonesia Stock Exchange. This study shows that the merger and acquisition strategy has no significant impact on the financial performance of companies on the Indonesia Stock Exchange.